(untitled) (Indian Journal of Geo-Marine Sciences (IJMS), 2025)
The goatfish species Mulloidichthys ayliffe Uiblein, 2011 (Mullidae) is reported for the first time from the Lakshadweep Archipelago, Eastern Arabian Sea, based on morphological and genetic studies of four specimens collected off Agatti Island. The fish is characterised by a distinct pattern of 4-5 blue stripes alternating with yellow, with the dorsal-most blue stripe crossing the lateral line beyond the base of the first dorsal fin, and the presence of 37 lateral line scales. The mitochondrial COI gene sequence of one M. ayliffe specimen was compared with two other sequences of M. ayliffe from South African waters, and found to be matching.